A Companion to Qualitative Research by Ewe Flick, Ernst von Kardoff and Ines Steinke. 2004 - Timseena, Bhanu (Nepalese Journal of Qualitative Research Methods, 2009)
doi: 10.3126/njqrm.v1i0.1977 Nepalese Journal of Qualitative Research Methods Vol.1 2007 pp.68-71